Characteristics, causes and significance of subsurface stress field of Beijing earth fissures group - Jishan Xu; Jianbing Peng; Yahong Deng; Haibo An; Zhenjiang Meng; Yan Wang; Zuodong Li (Geomatics, Natural Hazards & Risk)
The development of earth fissures in a certain area often has certain genetic correlations, which is called ‘group-developing phenomenon’ of earth fissures. So far, 41 earth fissures have developed in the Beijing area in the North China Plain. Surveys and exploration studies have shown that these earth fissures have a good correspondence relationship with the activities of the adjacent control faults. Accordingly, they can be divided into 9 zones. The mechanical analysis of these fissures groups reveals that they are roughly formed through 3 models, namely, ‘contemporaneous model’ (dip-slipping movement), ‘secondary model’ (strike-slipping movement) and ‘companion model’ (basin extension movement). The characteristics of this type (fault-controlled) earth fissures in combination with their distribution regularities in the area can be used to indicate that the distribution of subsurface tectonic stress fields is as a whole an extension of the NW-SE-trending, which is not completely consistent with the near E-W-trending extension of deep material migration. These analyses show that under the background of extensional deformation of the basin, the subsurface stress field characteristics of superficial formations are more complex, which not only embodies the movement form (unity) of the deep structure in whole, but also partially reflects the adjustability of the regional tectonic stress field.